The paediatric rheumatologist and orphan disease – a story without happy ending - Justyna Roszkiewicz (Rheumatology, 2016)
Orphan diseases are not a common challenge in the everyday practice of the rheumatologist. Despite their extremely rare occurrence one of the patients under our care developed one of them – neuronal ceroid lipofuscinosis, the most frequent neurodegenerative disease observed in the paediatric population. We report a case of 2-year-old girl diagnosed with oligoarticular form of juvenile idiopathic arthritis treated in our Department with steroids and methotrexate and staying in the stage of disease remission. During routine checkups at Outpatient Clinic we observed progressive deterioration of girls neurological condition resulting in ataxia, gait disturbances with no rheumatological cause behind and speech impairment. The appearance of the symptoms was accompanied by frequent episodes of epileptic seizures, with little clinical improvement on combined antiepileptic treatment. Magnetic resonance imaging that we performed showed a picture highly suggestive of neuronal ceroid lipofuscinosis – atrophy of the patients cerebrum and cerebellum. Genetic testing conducted resulted in the diagnosis of late infantile neuronal ceroid lipofuscinosis (LINCL).